The role of B cells in cancer development - Tan, Rongying; Nie, Manhua; Long, Wang (Frontiers in Oncology, 2022)
B cells play a critical role in adaptive immune responses mainly due to antigen presentation and antibody production. While the studies about the tumor-infiltrating immune cells so far demonstrated that the function of B cells in tumor immunity is quite different among various tumor types. The antigen presentation of B cells is mainly anti-tumoral, while the role of antibody production is controversial. Moreover, the immunosuppressive regulatory B cells are detrimental to anti-tumor immunity via the secretion of various anti-inflammatory cytokines. This review briefly summarizes the different roles of B cells classified by the primary function of B cells, antigen presentation, antibody production, and immunity regulation. Further, it discusses the potential therapeutic target of B cells in tumor immunity.